Perbandingan Leukosituria, Nitrit, Leukosit Esterase dengan Kultur Urin dalam Mendiagnosis Infeksi Saluran Kemih pada Anak - Sabriani, Jehan; Umboh, Adrian; Manoppo, Jeanette I. Ch. (Medical Scope Journal, 2021)
Abstract: Urinary tract infection (UTI) in children is the most common infection after upper airway infection. The diagnosis of UTI is based on urine culture, however, this examination takes a longer time and is quite expensive. Therefore, the diagnosis of UTI can also be confirmed by using leukocyturia, nitrite, and leukocyte esterase tests although they can not replace urine culture as the gold standard. This study was aimed to determine the accuracy of positive leukocyturia, positive nitrite, positive leukocyte esterase examination, combination of positive leukocyturia and nitrite examinations, positive leukocyturia and leukocyte esterase, and leukocyturia, nitrite, positive leukocyte esterase in diagnosing UTI. This was a literature review study. The results of the literature review showed that the range of accuracy of UTI diagnosis using positive leukocyte esterase examinations was 9-6.8%, positive nitrite was 2.8-100%, leukocyte esterase was 13.7-86%, combination of positive leukocyturia and nitrite had a sensitivity value of 33 %, and specificity of 94%, combination of positive leukocytic and leukocytic esterase had a sensitivity value of 70% and a specificity of 90%, and combination of leukocyturia, nitrite, and leukocyte esterase had an accuracy range of 100%. In conclusion, these examinations coul be used to confirm the diagnosis of UTI in children especially if the urine culture can not be performed on them.Keywords: urinary tract infection (UTI), leukocyturia, nitrite, leukocyte esterase, urine culture, children Abstrak: Infeksi saluran kemih (ISK) merupakan infeksi yang paling sering terjadi pada anak setelah infeksi saluran napas atas. Diagnosis ISK ditegakkan berdasarkan hasil pemeriksaan kultur urin, namun pemeriksaan ini membutuhkan waktu yang lama dan biaya yang cukup mahal. Pemeriksaan leukosituria, nitrit, dan leukosit esterase juga membantu dalam mendiagnosis ISK, namun ketiga pemeriksaan ini belum dapat menggantikan kultur urin sebagai baku emas untuk mendiagnosis ISK. Penelitian ini bertujuan untuk mengetahui seberapa besar ketepatan pemeriksaan leukosituria positif, nitrit positif, leukosit esterase positif, gabungan pemeriksaan leukosituria dan nitrit positif, leukosituria dan leukosit esterase positif, dan gabungan leukosituria, nitrit, leukosit esterase positif dalam mendiagnosis ISK. Jenis penelitian ialah literature review. Hasil penelitian menunjukkan kisaran ketepatan diagnosis ISK menggunakan pemeriksaan leukosituria positif yaitu 9-6,8%, nitrit positif sebesar 2,8-100%, leukosit esterase sebesar 13,7-86%, gabungan leukosituria dan nitrit positif memiliki nilai sensitivitas 33%, dan spesifisitas sebesar 94%, gabungan leukosituria dan leukosit esterase positif memiliki nilai sensitivitas 70% dan spesifisitas sebesar 90%, serta gabungan pemeriksaan leukosituria, nitrit, dan leukosit esterase memiliki kisaran ketepatan sebesar 100%. Simpulan penelitian ini ialah pemeriksan-pemeriksaan tersebut dapat membantu menegakkan diagnosis ISK pada anak terutama bila kultur urin tidak memungkinkan dilakukan.Kata kunci: infeksi saluran kemih (ISK), leukosituria, nitrit, leukosit esterase, kultur urin, anak